The Relationship of Organizational Culture to Employee Performance Mediated by Job Satisfaction - Achyar, Arfira Adzany; Firdausiah, Rr. Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of organizational culture on employee performance with job satisfaction as a mediating variable in expedition companies in Pekanbaru. Design/Methodology/Approach – This study employs an explanatory quantitative research design. Data were collected through questionnaires measured using a Likert scale. The sample consisted of 157 active permanent and contract employees of expedition companies in Pekanbaru selected using purposive sampling. Data analysis was conducted using Path Analysis with SmartPLS 3.0 by evaluating the outer and inner models to examine the direct and indirect relationships among the variables. Findings – The results indicate that organizational culture has a significant effect on employee performance. Furthermore, job satisfaction significantly mediates the relationship between organizational culture and employee performance. These findings suggest that strengthening organizational culture and enhancing employee satisfaction are important strategies for improving employee performance and supporting organizational competitiveness in the expedition industry. Originality/Value This research is original in empirically testing job satisfaction as a mediating variable between organizational culture and employee performance in expedition companies. The findings provide practical value by offering insights for managers to strengthen corporate culture in order to improve employee satisfaction and performance simultaneously.